Heavy metal characteristics and ecological threat assessment in water and sediments of Eniong Creek, Niger Delta, Nigeria - Jonah, Udeme Effiong; Anyanmu, Emeka Donald; Antai, Ekpo Eyo (Universitas Malikussaleh, 2024)
Heavy metal characteristics and ecological threat assessment in water and sediments of Eniong Creek, Nigeria was studied between August 2022 and January 2023 in 3 stations. Seven heavy metals were analyzed with standard methods and compared with quality Standard. Ecological threat was assessed in water using two metal pollution indices while six sediment quality assessment indices were used to access the sediment quality. Results showed that the mean concentrations of nickel, copper, cadmium and zinc in water sample exceeded the permissible limits set by National environmental (surface and groundwater) quality regulations for aquatic life, while copper and cadmium exceeded the permissible limits set by Canadian sediment standards quality for the protection of aquatic life in sediments in all the stations. The heavy metal pollution index (HPI) values exceeded the threshold (100) across the stations, ranging between 469.53 and 686.74 while comprehensive pollution index (CPI) ranged between 1.405 and 1.854, indicating moderate contaminated water. The sediment indices indicated that cadmium and copper were the major metallic pollutants. The indices indicated the following -contamination factor: copper (moderate) and cadmium (very high), degree of contamination (very high); ecological risk: cadmium and copper (high) while lead and zinc were moderate; potential ecological risk (high); quantification of contamination: cadmium and copper (anthropogenic); geo-accumulation index: cadmium (very highly polluted). The study revealed that the water body and sediments were polluted, attributed to anthropogenic activities.Keywords: Eniong Creek; Heavy Metals, Nigeria; Sediment; Water